AN ANALYSIS OF THE AFFECTIVE STRATEGIES USED BY STUDENTS IN SPEAKING PERFORMANCE - Adri Efriyandi (English Language Teaching and Research, 2017)
Speaking performance can be considered as activity of speaking in more formal setting such as speech and presentation. Speaker is expected to have positive attitude and confidence during the performance. Unfortunately, speaking can be so challenging due to problems that related to affective factors. Common affective problems in speaking in front of audience are anxiety and low-self esteem. When speakers are anxious, the symptom such nervousness, sweaty, and having bodily tense up, can inhibit them in having a good performance. Anxiety is stemmed from false belief about what audience may think about the performance, so the speaker experience fear. Low-self esteem relates to bad opinion and value that speakers put on themselves about their competence. One of the cause of low-self esteem is comparing oneself to another person. The act of comparing end with the bad feeling lack and inferior to other person. To combat low affective factors, there is affective strategy which can be applied before or during performance. this strategy can be divide as lowering anxiety, encouraging yourself, taking emotional temperature, and enhancing self-esteem. The use of affective strategy is expected to control speaker’s emotion in balance or even more positive during speaking performance. with applying affective strategy, speaker can be more relaxed and enjoy speaking. thus, this strategy is a solution for dealing with negative emotion that may occure in speaking. Keywords: Affective, performance, anxity, self-esteem